Euspermatozoa and paraspermatozoa in the volutid gastropod Odontocymbiola magellanica, Patagonia, Argentina, Southwestern Atlantic Ocean - Giménez, Juliana (2011)
The ultrastructure of mature spermatozoa and paraspermatozoa of Odontocymbiola magellanica is investigated. Euspermatozoa consist of: (1) a tall, conical acrosomal vesicle (with a short basal invagination, constricted anteriorly); (2) a rod-shaped, solid and highly electron-dense nucleus; (3) an elongate midpiece consisting of the axoneme sheathed by helical mitochondrial elements each exhibiting a dense U-shaped outer layer; (4) an elongate glycogen piece; (5) a dense annulus at the junction of the midpiece and glycogen piece; and (6) a short free-tail region. Paraspermatozoa of O. magellanica are vermiform and dimorphic. First type contain approximately 14-17 axonemes (arranged peripherally and interspersed with microtubules) and numerous oblong dense vesicles, numerous less dense (round) vesicles, and scattered mitochondria; the second type contains 38-45 axonemes peripherally arranged and closer to the core region of the cell and occasional mitochondria. Most of the euspermatozoal features of O. magellanica are also observed in many neotaenioglossans and neogastropods. However, the U-shaped outer layer of each mitochondrial element has only been previously reported in the Volutidae subfamily Zidoniinae. It is now reported here in the subfamily Odontocimbiolinae and may prove to be a diagnostic feature of the Volutidae family.